A Study on Health, Safety, Environment, and Ergonomics (HSEE) in Solar Power Plant - Shafira, Dinda Aulia Ilma; Abadi, Imam (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Solar energy has rapidly developed as a renewable energy source, but the aspects of Health, Safety, Environment, and Ergonomics (HSEE) in their operations have remained a concern. This study analysed the risks faced by workers and the environment at the Pantai Baru solar power plant using a risk analysis approach based on primary data from worker questionnaires and secondary data from literature reviews and field observations. The findings showed that the health aspect included heat stress such as prolonged under direct sunlight and exposure to toxic materials, these materials include heavy metals such as cadmium (Cd) and lead (Pb), which are commonly used in photovoltaic (PV) technology to enhance efficiency but are known to be carcinogenic and hazardous even at low doses. The safety aspect covered electrical hazards, fire hazards, and falling risks, all of which were exacerbated by suboptimal working conditions. From an environmental perspective, solar power plants caused ecosystem damage, required large land areas, and faced challenges in recycling solar panels and batteries. Ergonomic risks were also identified, but the questionnaire results indicated that musculoskeletal injuries were not a significant issue for solar power plant workers. This study concluded that most HSEE sub-variables were relevant to the risks associated with solar power plants, except for musculoskeletal injuries. Therefore, implementing risk mitigation strategies, improving workplace design, and enforcing stricter environmental policies were necessary to ensure safe, efficient, and sustainable solar power plant operations.